Impact of improving dietary amino acid balance for lactating sows on efficiency of dietary amino acid utilization and transcript abundance of genes encoding lysine transporters in mammary tissue,. Issue 11 (1st November 2016) - Huber, L.; de Lange, C. F. M.; Ernst, C. W.; Krogh, U.; Trottier, N. L.
ABSTRACT: Lactating multiparous Yorkshire sows ( n = 64) were used in 2 experiments to test the hypothesis that reducing dietary CP intake and improving AA balance through crystalline AA (CAA) supplementation improves apparent dietary AA utilization efficiency for milk production and increases transcript abundance of genes encoding Lys transporter proteins in mammary tissue. In Exp. 1, 40 sows were assigned to 1 of 4 diets: 1) high CP (HCP; 16.0% CP, as-fed basis; analyzed concentration), 2) medium-high CP (MHCP; 15.7% CP), 3) medium-low CP (MLCP; 14.3% CP), and 4) low CP (LCP; 13.2% CP). The HCP diet was formulated using soybean meal and corn as the only Lys sources. The reduced-CP diets contained CAA to meet estimated requirements for essential AA that became progressively limiting with reduction in CP concentration, that is, Lys, Ile, Met + Cys, Thr, Trp, and Val. Dietary standardized ileal digestible (SID) Lys concentration was 80% of the estimated requirement. In Exp. 2, 24 sows were assigned to the HCP or LCP diets. In Exp. 1, blood samples were postprandially collected 15 h on d 3, 7, 14, and 18 of lactation and utilization efficiency of dietary AA for milk production was calculated during early (d 3 to 7) and peak (d 14 to 18) lactation. Efficiency values were estimated from daily SID AA intakes and milk AA yield, with corrections for maternal AA requirement for maintenance and AA contribution from body protein losses. In Exp. 2, mammary tissue was biopsied on d 4 and 14 of lactation to determine the mRNA abundance of genes encoding Lys transporter proteins. In peak lactation, Lys, Thr, Trp, and Val utilization efficiency increased with decreasing dietary CP (linear for Trp and Val, P < 0.05; in sows fed the MHCP diet vs. sows fed the HCP diet for Lys and Thr, P < 0.05). Total essential and nonessential 15-h postprandial serum AA concentrations increased with decreasing dietary CP (linear, P = 0.09 and P < 0.05, respectively), suggesting increased maternal body protein mobilization. Transcript abundance of several genes involved in Lys transport in mammary tissue did not differ between sows fed the LCP and HCP diets. Feeding lactating sows low-CP diets supplemented with CAA increases the efficiency of utilizing dietary Lys, Thr, Trp, and Val for milk protein production but is unrelated to abundance in mRNA of genes encoding Lys transport proteins in the mammary gland. Dietary Lys utilization for milk protein production in lactating sows appears to be optimized when crystalline Lys is included at a minimum of 0.10% in a diet containing 15.70% CP.